L’influence politique des discours chrétiens sur les droits reproductifs au Costa Rica et au Nicaragua - Laura Fuentes Belgrave (Nuevo mundo - Mundos Nuevos, 2013)
The political engagements of Catholic Church and Evangelical Churches in a secular state as Nicaragua and in a denominational state as Costa Rica, led to ban abortion and in vitro fertilization such as to restrict morning-after pill access. These churches have formed an alliance for “the protection of life of the unborn” at the expense of women rights. The religious field takes over political arena through political elites. Theses ones use sexual and reproductive rights to reach electoral purposes.